FRI0127 Eular Recommendations for the Use of Imaging in Spondyloarthritis in Clinical Practice. (10th June 2014) - Mandl, P.; Navarro-Compán, V.; Terslev, L.; Aegerter, P.; van der Heijde, D.; D'Agostino, M.-A.; Baraliakos, X.; Juhl Pedersen, S.; Jurik, A.G.; Naredo, E.; Schueller-Weidekamm, C.; Weber, U.; et al.
Abstract : Objectives: To develop evidence-based recommendations on the use of imaging in the clinical management of both axial and peripheral spondyloarthritis. Methods: The task force comprised an expert group of 21 rheumatologists, radiologists and methodologists from 11 countries. Twelve key questions on the role of imaging in SpA were generated using a process of discussion and consensus. Imaging modalities included conventional radiography (CR), ultrasound (US), magnetic resonance imaging (MRI), computed-, positron emission- and single photon emission computed tomography, dual-emission x-ray absorptiometry (DXA) and scintigraphy. Experts used research evidence obtained from a systematic literature review using MEDLINE and EMBASE to develop a set of 10 recommendations. The strength of recommendation (SOR) was assessed by the group members using a visual analogue scale. Quality assessment of the included studies was performed using the QUADAS-2 tool. Results: A total of 7550 references were identified in the search process, from which 157 studies were included in the systematic review. Ten recommendations were produced encompassing the role of imaging in making a diagnosis of axial SpA or peripheral SpA, monitoring inflammation and damage, predicting outcome, response to treatment, and detecting spinal fractures and osteoporosis (OP). The SOR for each proposition varied, but was generally very high (mean 8.9-9.5). Selected aspects of the recommendations are given below (NOT all recommendations and NOT the exact wording, due to space constraints): CR of the sacroiliac joint (SIJ) is recommended as the first imaging method to diagnose sacroiliitis as part of axial SpA, while MRI is an alternative first imaging method in certain cases. US or MRI may be used to detect peripheral arthritis, tenosynovitis, bursitis and particularly peripheral enthesitis, which may support the diagnosis of SpA. MRI of the SIJ and/or spine may be used to assess and monitor disease activity, while CR of the SIJ and/or spine may be used for long-term monitoring of structural damage, particularly new bone formation in axial SpA. In patients with AS (not nonradiographic axial SpA), initial CRs of the lumbar and cervical spine are recommended to detect syndesmophytes, which are predictive of development of new syndesmophytes. MRI (vertebral corner inflammatory lesion) may also be used to predict development of new radiographic syndesmophytes. When spinal fracture in axial SpA is suspected, CR is the recommended initial imaging method. In axial SpA without radiographic syndesmophytes in the lumbar spine, OP should be assessed by hip and AP-spine DXA. Conclusions: Ten recommendations for the role of imaging in the clinical management of SpA were developed using research-based evidence and expert opinion. Disclosure of Interest: P. Mandl: None declared, V. Navarro-Compán: None declared, L. Terslev: None declared, P. Aegerter: None declared, D. van der Heijde: None declared, M.-A. d'Agostino: None declared, X. Baraliakos: None declared, S. Juhl Pedersen: None declared, A. G. Jurik: None declared, E. Naredo Grant/research support: MSD, Spanish Foundation of Rheumatology, Speakers bureau: Abbvie, Roche Pharma, BMS, Pfizer, UCB, GE, ESAOTE, C. Schueller-Weidekamm: None declared, U. Weber Consultant for: AbbVie, M. Wick: None declared, E. Filippucci: None declared, P. Conaghan: None declared, M. Rudwaleit Consultant for: Roche, MSD, Pfizer, Novartis, UCB, Speakers bureau: AbbVIe, BMS, Chugai, G. Schett: None declared, J. Sieper: None declared, S. Tarp: None declared, H. Marzo-Ortega Speakers bureau: AbbVie, MSD, Janssen, Pfizer, UCB, M. Østergaard: None declared DOI: 10.1136/annrheumdis-2014-eular.2204